Jatsiyah Financing System : Fintech Berbasis Waqaf-Crowdfunding untuk Tercapainya Kemaslahatan Nelayan ABK - Wahyuni, Sri; Kusumaningrum, Septiana Indriani (Universitas Trunojoyo Madura, 2019)
AbstractIndonesia is one of the countries endowed with abundant marine resources. Based on LIPI data in 2019, Indonesia's marine potential reaches Rp. 1772 trillion. In addition, the Ministry of Maritime Affairs and Fisheries data report reveals that fisheries production and GDP from 2017-2018 shows increasing numbers. The high potential of this fishery brings us to a big question, what is the current condition of the fishermen's economy. In 2015 the Central Statistics Agency released data that 25% of Indonesia's poor population work as fishermen. One of the things that causes fishermen poverty is the existence of an unfair sharing system between ABK fishermen and boat owner fishermen. Of course, this phenomenon requires a solution, one of which is a fishing boat procurement project based on humanity, which is professionally managed, sustainable and can be a productive asset for Muslims. Besides that, in implementing the ship procurement project, funding support is needed, one of which is cash waqf which is collaborated with financial technology to raise cash waqf funds from the community. Therefore, the authors initiated the Jatsyiah Financing System (JAFIS). JAFIS is a crowdfunding donation based platform that collects cash waqf funds from the community, to be further utilized to implement the procurement project for fisherman-based fishing vessels. The main vision of JAFIS is